Compost Oil Palm and Indigenous Endophytic Fungi Effect on Basal Stem Rot in Oil Palm Seedling - . Lisnawati; Hamidah Hanum; Ahmad Rafiqi Tantawi (Syiah Kuala University, 2015)
Basal stem rot (BSR) caused by Ganoderma is an important disease of oil palm in North Sumatra, Indonesia. Control of BSR is complex, because the disease occurs in the dynamic environment at the interface of the roots with soil. Compost with endophytic fungi as a biological fertilizer offer possible advantages and eventually suppressed ganoderma growth. A study using two compost oil palm (empty fruit bunch and palm oil midrib-leaf compost) containing indigenous endophytic fungi (Trichoderma koningii, T. viride, and Aspergillus sp.) singly and in a mixture was conducted to determine potential of them to control Ganoderma. The result showed that 16 weeks after artificial inoculation, all treatments aren't significant difference reduced BSR incidence but compost containing endophytic fungi have potential to inhibit the pathogen showed BSR incidence in a mixture treated lower than singly treated seedlings